Biomechanical in vitro evaluation of three stable internal fixation techniques used in sagittal osteotomy of the mandibular ramus: a study in sheep mandibles - de Olivera, Leandro Benetti; Sant'Ana, Eduardo; Manzato, Antonio Jose [UNESP]; Bunemer Guerra, Fabio Luis; Arnett, G. William (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2012)
Among the osteotomies performed in orthognathic surgery, the sagittal osteotomy of the mandibular ramus (SOMR) is the most common, allowing a great range of movements and stable internal fixation (SIF), therefore eliminating the need of maxillomandibular block in the postoperative period. Objectives: The purpose of this study was to evaluate the biomechanical resistance of three national systems used for SIF in SOMR in sheep mandibles. Material and methods: The study was performed in 30 sheep hemi-mandibles randomly divided into 3 experimental groups, each containing 10 hemi-mandibles. The samples were measured to avoid discrepancies and then subjected to SOMR with 5-mm advancement. In group I, 2.0x12 mm screws were used for fixation, inserted in an inverted "L" pattern (inverted "L" group). In group II, fixation was performed with two 2.0x12 mm screws, positioned in a linear pattern and a 4-hole straight miniplate and four 2.0x6.0 mm monocortical screws (hybrid group). In group III, fixation was performed with two-hole straight miniplates and eight 2.0x6.0 mm monocortical screws (mini plate group). All materials used for SIF were supplied by Osteosin - SIN. The hemimandibles were subjected to vertical linear load test by Kratos K2000MP mechanical testing unit for loading registration and displacement. Results: All groups showed similar resistance during mechanical test for loading and displacement, with no statistically significant differences between groups according to analysis of variance. Conclusion: These results indicate that the three techniques of fixation are equally effective for clinical fixation of SOMR.
Keywords: Mandible; Osteotomy; Bone plates; Bone screws